2023
DOI: 10.1021/acs.langmuir.2c03417
|View full text |Cite
|
Sign up to set email alerts
|

Spherical DNA for Probing Wettability of Microplastics

Abstract: Wettability of microplastics may change due to chemical or physical transformations at their surface. In this work, we studied the adsorption of spherical nucleic acids (SNAs) with a gold nanoparticle core and linear DNA of the same sequence to probe the wettability of microplastics. Soaking microplastics in water at room temperature for 3 months resulted in the enhancement of SNA adsorption capacity and affinity, whereas linear DNA adsorption was the same on the fresh and soaked microplastics. Drying of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…DNA oligonucleotides have been extensively used in nanotechnology over the past few decades owing to their programmable structure, low cost, high stability, and their unique base-pairing rule. Adsorption of DNA on nanomaterials has been applied for molecular recognition, , catalysis, and materials characterization …”
Section: Introductionmentioning
confidence: 99%
“…DNA oligonucleotides have been extensively used in nanotechnology over the past few decades owing to their programmable structure, low cost, high stability, and their unique base-pairing rule. Adsorption of DNA on nanomaterials has been applied for molecular recognition, , catalysis, and materials characterization …”
Section: Introductionmentioning
confidence: 99%
“…While a growing number of studies have recognized and considered adsorption of DNA onto MPs, ,, a more extensive body of work has considered DNA adsorption onto soil components (summarized in Pietramellara et al and Yu et al) , which can help guide future studies on the topic. However, these soil components may have some different adsorbent behavior compared to MPs.…”
Section: Resultsmentioning
confidence: 99%
“…For example, our team recently observed that upon soaking microplastics in water, the adsorption efficiency of biomolecules such as spherical DNA dramatically changed due to the change in the wettability of microplastics. [ 159 ] Such adsorption studies should therefore be carried out systematically when assessing potential degradation catalysts for different microplastic substrates. These results can inform better experimental designs and, potentially, the engineering of more effective catalysts in terms of binding and activity. Scaling up and practical implementation of biotic, abiotic, and mixed catalytic degradation techniques are areas that require further investigation and development.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%